Recent Trends in Data Science and Soft Computing Proceedings of the 3rd International Conference of Reliable Information and Communication Technology (IRICT 2018) - Saeed, Faisal; Gazem, Nadhmi; Mohammed, Fathey; Busalim, Abdelsalam; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the proceedings of the 3rd International Conference of Reliable Information and Communication Technology 2018 (IRICT 2018), which was held in Kuala Lumpur, Malaysia, on July 23-24, 2018. The main theme of the conference was "Data Science, AI and IoT Trends for the Fourth Industrial Revolution." A total of 158 papers were submitted to the conference, of which 103 were accepted and considered for publication in this book. Several hot research topics are covered, including Advances in Data Science and Big Data Analytics, Artificial Intelligence and Soft Computing, Business Intelligence, Internet of Things (IoT) Technologies and Applications, Intelligent Communication Systems, Advances in Computer Vision, Health Informatics, Reliable Cloud Computing Environments, Recent Trends in Knowledge Management, Security Issues in the Cyber World, and Advances in Information Systems Research, Theories and Methods.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence